IMF Staff papers : Volume 7 No. 2. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1959)
This paper discusses that the need for financing accounts and for integrated income and financing accounts is to be found in the fact that the income accounts are deficient in two respects as a source of data on the variables in the Keynesian analysis. Investment as measured in the income accounts is not a wholly satisfactory measure of the investment variable of income analysis; and the income accounts omit entirely data on money and other financial assets, which are variables that play roles in the income analysis as necessary as those of saving and investment. The need for financing accounts is the need to measure the strategic variable, money, and to provide data on other financial assets in a form in which the causes and effects of changes in the economy's preferences for money and other types of financial asset can be analyzed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet